2017
DOI: 10.3390/sports5020042
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eccentric Strength in 180° Turns in Female Soccer Players

Abstract: Previous studies have reported an association between eccentric strength (ECC-STR) and change of direction (COD) ability. Little is known about how ECC-STR facilitates COD maneuvers. The aim of this study was to examine the role of ECC-STR during a 180° COD task in 18 female soccer players. Each player performed six trials of a 180° COD task whereby three-dimensional motion data from 10 Qualisys Pro-Reflex infrared cameras (240 Hz) and ground reaction forces (GRFs) from two AMTI force platforms (1200 Hz) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
224
5
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(253 citation statements)
references
References 25 publications
19
224
5
5
Order By: Relevance
“…It has previously been suggested that four major physical qualities exert a significant influence on deceleration ability, namely: dynamic balance, eccentric strength, power and reactive strength (22). In studies examining change of direction (COD) performance necessitating the production of large braking forces, it has been shown that high lower limb eccentric strength capabilities increase braking force potential, thereby promoting whole-body deceleration (19,20,24,36). Interestingly, the quadriceps have been suggested to be the 'primary' muscle group regulating sudden deceleration ability (14) due to their role in resisting knee flexion (6) and facilitating the absorption and distribution of eccentric loads at the knee (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that four major physical qualities exert a significant influence on deceleration ability, namely: dynamic balance, eccentric strength, power and reactive strength (22). In studies examining change of direction (COD) performance necessitating the production of large braking forces, it has been shown that high lower limb eccentric strength capabilities increase braking force potential, thereby promoting whole-body deceleration (19,20,24,36). Interestingly, the quadriceps have been suggested to be the 'primary' muscle group regulating sudden deceleration ability (14) due to their role in resisting knee flexion (6) and facilitating the absorption and distribution of eccentric loads at the knee (22).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the quadriceps have been suggested to be the 'primary' muscle group regulating sudden deceleration ability (14) due to their role in resisting knee flexion (6) and facilitating the absorption and distribution of eccentric loads at the knee (22). Only one previous study, however, has examined the influence of eccentric KE strength on the ability to decelerate rapidly prior to a COD (20). Importantly, here, players with greater eccentric KE strength decelerated more rapidly during the steps immediately prior to a COD, thereby permitting a faster approach velocity, and a significantly faster COD performance time.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that the H-L group would significantly improve their performance during the 180º COD task, and improve to a greater extent than the L-H group. This hypothesis was based on previous literature, which indicates that eccentrically-accentuated training can enhance athlete's ability to produce and control force eccentrically, allowing for greater decelerations from faster approach velocities during COD tasks involving a large braking component [20,[23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Lockie and colleagues [22] found that emphasizing deceleration during speed and agility training improved unilateral strength, as well as performance in COD tests and 40 m sprint time. It has been suggested that eccentric overload training resulting in enhanced eccentric strength can improve athlete's COD performance during the braking and plant phases, as athlete's who are able to produce greater force eccentrically are able to produce greater decelerations from faster approach velocities [20,23]. In support of this, de Hoyo and colleagues [24] found that ten weeks of eccentric overload training resulted in improved kinetic parameters including time spent braking, relative peak braking, and relative braking impulse during COD tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this performance-injury conflict should once again be managed during the rehabilitation process. Prior to exposing ACLr patients to tasks at maximal approach velocities during a CoD test, practitioners should ensure that patients display appropriate CoD mechanics [20,21,35,45] and the requisite physical capacities to tolerate the associative knee joint loading [37,63,65,72,83]. Furthermore, approach velocities (and distances) should be gradually increased as the athlete progress and moves closer to return to sport.…”
Section: Practical Applicationsmentioning
confidence: 99%